Evaluation of Open and Green Space Systems in the Context of Urban Livability - Hizli, Ozne; Aktan, Esin Ozlem Aktuglu (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2023)
Urban that has overgrown in recent years have affected human lifestyle and ecological balance in a negative way. Open and green spaces decreased. With this, unhealthy urban conditions occur. Therefore, urban is becoming more unlivable. The aim of this study, starting from the problem of insufficient/unqualified open and green areas in urban, is to show that cities are more livable when the open and green spaces system is designed.The top 10 livable cities ranking the world cities are listed by 6 different institutions and the same cities included in this list are selected. The open and green areas of 4 different selected cities were examined. In the scope, two basic concepts are based on: open-green space systems and urban livability. As a result of the study, it has been seen that open and green space systems affect cities more livable. Therefore, open and green areas are planned systematically for maximum benefit with a sustainable approach. However, systems also need new approaches at some points. At this point, a hypothetical open green space system is proposed in this study. The concept of urban liveability and open and green spaces, an index of urban liveability, are explained. Then, open and green space systems in the literature are clarified with examples. To show the relationship between urban liveability and open green spaces, the research results done by different institutions, the most overlapping cities have been selected according to the top 10 list of most liveable cities list. The value of this study to make itself original and the literature contribution is that at the end of the research, a new open and green system was suggested based on the open and green systems in the literature.
Keywords: Greenspace planning; liveable cities; rank; open and green spaces; urban; green system; urban liveability; QUALITY-OF-LIFE; Architecture